The stock market effect of air pollution: evidence from China. Issue 36 (1st August 2016) - Li, Q.; Peng, C.H.
ABSTRACT: In financial studies, environmental stimuli such as sunshine, temperature, and daylight are often used as proxies for people's collective mood swings to test their effects on the stock market. China has experienced serious air pollution problems in recent years, and Chinese public awareness of air pollution has soared. In this paper, we use China as a natural experiment to investigate the effect on stock returns of depressed moods induced by air pollution. Daily air-pollution data from 2005 to 2014 are analysed and the results obtained from the empirical research show that a contemporaneous negative and a two-day lagged positive relationship exists between air pollution levels and stock returns over this time period. The relationship is mediated by the influence of air pollution on investment decisions. The results also indicate that the effect is weakened for companies that protect air quality, but no stronger effect is detected for polluting companies. The findings imply that air pollution is a behavioural factor with some connection to stock returns in China.